Dampak Simpanan dan Bonus Wadiah terhadap Net Imbalan pada Perbankan Syariah Indonesia (2018-2023) - annisa, maulidya; Hestya Budianto, Eka Wahyu (Jurnal Perbankan Syariah, 2024)
This research serves to determine and examine how Wadiah Current Account Deposits, Wadiah Savings Deposits, and Wadiah Bonuses impact Net Income (NI). In addition, this study also looks at how firm size serves as a moderating variable in the relationship between the independent variables (Wadiah Current Account Deposits, Wadiah Savings Deposits, and Wadiah Bonus) and the dependent variable (Net Rewards).This study uses a quantitative approach by using secondary data from the annual reports of the banks under study.The number of five sample companies registered with OJK from 2018 to 2023 is a purposive sample. This study evaluates the relationship between independent and dependent variables through the use of panel data regression analysis and moderated regression analysis (MRA). The purpose of this study is to assess whether Wadiah Current Accounts, Wadiah Savings, and Wadiah Bonus affect Net Return (NI), and whether Company Size moderates the relationship between these independent variables.